Construction of Project Management Using Information System - Alfawaz, Khaled Mofawiz; Aljedani, Fahd Mohammed (Communications in Mathematics and Applications, 2022)
Information is playing a vital role of every concerns project management processes. The activities of organization’s project management, desires to attain an excellent flow of information. This task can be done through to build a high quality information system to that concern. This paper concentrates the present status of information systems in the function of construction project management for the huge corporation and government agencies in Saudi Arabia. The innovative conceptual model names as Information System Success (ISS) is built to obtain the barriers of information system in project constructions as well as independent variables are introduced. With the assistance of ISS model, the researcher can create a survey to verify the achievement of the information system and the autonomous variables that influence the information system within the population data. The results will explain the improvements of Saudi Arabia’s large corporation government agencies construction project. Moreover, the result indicates that the independent variables have focusing the effect of the information system such as IT infrastructure, organizational competence along with management support.